The role of activating work ethic in reducing manifestations of administrative corruption: An exploratory study of the views of administrative leaders in Koya University in the Kurdistan Region of Iraq - Aljaf, Nazima Ahmed; Sadq, Zana Majeed; Hassan, Ryam Salah (Journal of University of Human Development, 2017)
This study seeks to activate the job carrier ethic in curbing the phenomenon of administrative corruption. To achieve the objectives of this study secondary data collected to clarify the concepts of both job carrier ethic and administrative corruption. In addition to design and development a survey questionnaire distributed to the administrative leadership of deans and their assistants as well as the heads of scientific departments at Koya University Kurdistan Region –Iraq. The study problem embodied in a basis question that: What is the role of job carrier ethic in the reduction of administrative corruption and its demonstration in the view of the respondents. Two main hypotheses will be tested: Correlation hypothesis: there is a statistically significant correlation between the activation of job carrier ethic in reducing the phenomenon of administrative corruption. 2. Impact hypothesis: There is a significant impact of job carrier ethic on reducing the phenomenon of administrative corruption. SPSS program used along with a range of statistical methods for the purposes of analyzing the questionnaire items including percentages and frequency to analyze the respondent's answers of paragraphs contained in the questionnaire. In order to testing the study hypothesis, the study will rely on the correlation coefficient (Pearson) to test the correlation between study variables. Moreover, multiple regression analysis will be used to determine the impact of the independent variable (job carrier ethic) on dependent variable (administrative corruption). The study found that there is a positive correlation and an impact between activate the job carrier ethic in curbing the phenomenon of administrative corruption. Based on the above, this study recommends the necessitate of university management to work to make greater efforts to infuse the concept of ethics career as one-dimensional organizational and regulatory environment appropriate to provide the personnel as well as introduce the concept of career work ethic in institutes and universities within their curricula independent in the years of the study.